Factores tecnológicos y su incidencia en los procesos de planificación del Gobierno Autónomo Descentralizado Municipal de Loja, año 2024 - Guamán Díaz, Gabriela Anabell (2025)
The objective of this research is to determine the main technological factors that influence the planning processes of the Municipal GAD of Loja. Currently, technologies play a fundamental role in all daily activities, completely transforming institutional management. The importance of ICT for the GAD lies in its ability to optimize processes, improve decision-making, and promote transparency and citizen participation. A mixed-methodological approach was used, including qualitative and quantitative data, through a systematic literature review, surveys, and interviews. This approach provided insights into the functioning of the GAD's planning department and the technological tools employed, as well as the perception of ICT use in process efficiency. The results revealed that the GAD has made significant efforts to integrate technology into daily management, resulting in considerable time and resource savings while streamlining management and decision-making processes. The key technological factors identified include technological infrastructure, staff training, system integration, and the perceived usefulness and ease of use of technologies. The findings highlight a technological impact that has facilitated the management of the planning department of the Municipal GAD of Loja.